A User study on virtual tutor mobile augmented reality from undergraduate medical student perspectives - Nur Athirah Hassan Basri,; Rahmita Wirza O.K. Rahmat,; Hizmawati Madzin,; Rafidah Hod, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Mobile Augmented Reality (MAR) is another fascinating educational innovation with broad potential. It allows for new educational tactics, particularly in medicine. The concept of MAR can help learning activities in several ways, including allowing faster access to information in the mobile platform, increasing student motivation, making the learning process easier and more efficient, and aiding students in better understanding important concepts. However, three things needed to be considered: interface design, the usefulness of Augmented Reality (AR), technical problems with the use of AR applications, and teacher training on the use of AR applications. Without a well-designed interface and guidance for the students, AR technology can be too complicated to use, especially for those who are not familiar with the technology. An interface should be easy to remember and learnt by the user on how to best utilize it. In this study, we present a virtual tutor in the tutorial section, named Otus, which aids the students on how to use a MAR application called BARA (Brain Anatomy Revision Application). Our goal is to create a fluid interface flow in this MAR application for education that includes a virtual tutor. By including a virtual tutor, users can quickly increase their comprehension of how to use the application on their own. We ran an experiment to evaluate the usefulness of the Otus, comparing two groups: one was the experimental group, which consisted of 12 students using BARA with Otus in the tutorial, and the other was control group, which consisted of 12 students using BARA without Otus. We concluded from our questionnaire and observations that the experimental group was able to experience AR step by step and required more time to navigate the MAR app.